The Effect of Facilities and Service Quality on Inpatient Satisfaction at Ngimbang Hospital, Lamongan Regency - Siska Maulana Dewi; Imam Syairozi; Nurul Badriyah (Sean Institute, 2024)
This study aims to analyze the influence of facilities and service quality on inpatient satisfaction at the Ngimbang Regional General Hospital (RSUD), Lamongan Regency. The study used a quantitative approach with the population of all inpatients at Ngimbang Hospital during the study period of 804 patients. The sample was determined using the Slovin formula with an error rate of 10%, so that 89 respondents were obtained. Data was collected through observations, interviews, and Likert scale questionnaires. The independent variable of the study was facility and quality of service, while the bound variable was patient satisfaction. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression, multiple correlation, determination coefficients, partial tests, and simultaneous tests. The results showed the regression equation Y = 1.049 + 0.315X1 + 0.386X2. Facilities had a significant effect on patient satisfaction with a t-value of 6.746 and a significance of 0.000. The quality of service also had a significant effect with a t-value of 7.377 and a significance of 0.000. Simultaneously, facilities and service quality had a significant effect on patient satisfaction with an F value of 135.852 and a significance of 0.000. An R Square value of 0.760 indicates that 76% of the variation in patient satisfaction is explained by facilities and quality of service. The service quality variable is the dominant factor because it has the highest regression coefficient and standardized beta.